Perceived Education Quality and Its Impact on Students’ Satisfaction at Pokhara University of Nepal - Ojha, Deepak; Ranabhat, Deepesh; Dhungana, Bharat Ram; Sapkota, Pradeep (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: Based on the Service Performance (SERVPERF) model and expectancydisconfirmation theory, this study investigates how five education quality dimensions (i.e., physical facilities, curriculum design, teachers’ expertise, student support, and financial assistance) shape student satisfaction at Pokhara University.Design/methodology/approach: This study employed a cross-sectional design, surveying 400 undergraduate and postgraduate students proportionally sampled from four constituent colleges of Pokhara University using quota and convenience methods. Data were analyzed using SPSS and Structural Equation Modeling (SEM).Findings: The findings revealed that curriculum design and student support are the strongest predictors of student satisfaction, followed by financial assistance and teachers’ expertise, while physical facilities do not have a meaningful impact.Conclusion: This study advances the behavioral understanding of service quality in higher education by demonstrating that intangible dimensions significantly outweigh tangible ones in driving student satisfaction at the constituent colleges of Pokhara University.Implications: It extends established service quality frameworks into Nepal’s higher education context and delivers actionable insights for university administrators and policymakers.Originality/value: This study fills a critical gap by applying established service quality models to Nepal’s underexplored higher education context, blending the roles of tangible and intangible factors in shaping student satisfaction.JEL Classification: I21, I22, I23, R53